Pengaruh Good Government Governance, Pengendalian Intern, dan Budaya Organisasi Terhadap Kinerja Organisasi Perangkat Daerah (OPD) - Yudhasena, I Gede Iswara; Putri, I G. A. M. Asri Dwija (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p17, 2019)
The Regional Devices Organization (OPD) of Karangasem Regency needs to pay attention to the application of the principles of Good Government Governance (GGG), internal control and organizational culture to improve regional organizational performance (OPD). This study aims to obtain empirical evidence of the effect of GGG, internal control and organizational culture on regional organizational performance (OPD) in Karangasem Regency. The method of data collection in this study is the survey method using questionnaire techniques. The sampling method uses a saturated sampling technique. The sample used amounted to 3 employees in each regional device organization (OPD) with a total number of 32 (OPD). The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the effect of GGG, internal control and organizational culture has a positive effect on the performance of regional organizational organizations (OPD) in Karangasem Regency. Keywords : Good Government Governance, internal control, organizational culture, Regional Organizational Performance (OPD).